(3QjMGf GdGdHGH hQjYGf GdTHGH aj eQGJH GdBOGHs - (3eMeO Hf EHQGgje Hf NjQI, CHh GdbGSe Hf GdehGYjfj GdbQWHj GdETHjdj,J (B564 (3g` s
(3ChdgG (B:s
(3QH ChRYfi Cf CTcQ fYeJc GdJi CfYeJ Ydi hYdi hGdOi gPG cJGH febJg HGLJeGY GdacQ Jfejb GdbGWa dCRgGQ GdHSGJjf s
(3BNQgG (B:s
(3Gbd Ydi Hf CHj WGdH QVi Gddg Yfg ajeG jQhi CfeG CfJ Whd YeQ HgG eG YeQJ ai GdSGYg GdJi CfJ ajgG hGdMeO ddg Pi GdYah hGdEeJfGf s
(3Cced JCdjag SfI (B557s
(3HChdg agQSJs
(3Hg fXGe GdJYbjHIs
(3GdfSNI HgG MhGT s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B198s
Keywords: (3GdCOHs